ANTIOXIDANT PROPERTIES AND INHIBITORY EFFECT OF ETHANOLIC EXTRACT OF STRUCHIUM SPARGANOPHORA (EWURO ODO) LEAF ON α - AMYLASE AND α – GLUCOSIDASE ACTIVITIES - Oboh, Ganiyu; Akinyemi, A J; Ademiluyi, A O (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Recent studies have shown that vegetables consumption could lower the risk of diabetes mellitus. Therefore, this study sought to investigate the inhibitory effect of Struchium sparganophora (Ewuro Odo) leaf on key enzyme linked to type-2 diabetes (α-amylase and α-glucosidase) as well as assessing the effect of blanching (a commonly practiced food processing technique) of this leafy vegetable on these key enzymes. Fresh leaves of Struchium sparganophora were blanched in hot water for 10 minutes, and the 70% ethanolic extracts of the fresh and blanched vegetables were prepared and used for subsequent analysis. The antioxidant properties and interaction of the extracts on α - amylase and α - glucosidase activities was determined in vitro. The result revealed that Struchium sparganophora leaf scavenged DPPH free radical and also inhibited α - amylase and α - glucosidase activities in a dose dependent manner (0.05 -0.2 mg/ml). However, blanching of this leafy vegetables caused a significant (P<0.05) increase in the antioxidant properties as typified by the DPPH radical scavenging ability and reducing property but decrease their ability to inhibit α - amylase and α - glucosidase activities. This antioxidant properties and enzyme inhibition could be part of the mechanism by which green leafy vegetables exert their anti-diabetic properties. However, blanching of the vegetable could reduce their ability to inhibit both α - amylase and α - glucosidase activity, but enhance their antioxidant properties in vitro.